Impactos da pandemia de COVID 19 na saúde física e mental de empresários e funcionários do comércio de Santana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The Covid-19 pandemic has had great repercussions and impacts on the lives of thousands of people around the world, both in social, economic and cultural aspects. With the emergence of the virus, protective measures were enacted, bringing new routines to the lives of all individuals. Such measures directly impacted the physical, mental and psychological health of the population. In view of this context, the present study aims to identify the impacts caused by the COVID-19 pandemic on the physical and mental health of entrepreneurs and commercial employees in Santana do Livramento. Questionnaires were prepared using Google Forms and applied to 50 companies in the city. The form was disseminated through social networks, and was also applied face-to-face in some organizations. The data analysis technique is statistical, descriptive. At the end of the survey, a sample of 162 respondents was obtained. As a result, it was possible to perceive the impacts of Covid-19 on the participants' lives, in aspects related to physical, emotional, social well-being, in addition to other psychological factors such as anxiety, depression, anguish, in the midst of the pandemic period. The greatest impact occurs in the psychosocial aspect, as a result of the fatigue, stress and anxieties associated with the coronavirus, as well as the bad mood and sadness, reported as frequent by the research participants.
Impacts of the COVID 19 pandemic on the physical and mental health of entrepreneurs and employees of business in Santana do Livramento
Keywords: Covid-19; Adoecimento no trabalho; Pandemia; Illness at work; Pandemic; CNPQ::CIENCIAS SOCIAIS APLICADAS